Risk factors for 90-day unplanned readmission after open posterior lumbar fusion in the elderly - Lyu, Hao-Zhen; Hu, Lang (Frontiers in Neurology, 2026)
BackgroundThe inescapable trend of an aging population has made lumbar fusion increasingly common in elderly individuals. This study aimed to explore the risk factors associated with unplanned readmission within 90 days after open posterior lumbar fusion (OPLF) in elderly patients (≥ 60 years old).MethodsWe retrospectively analyzed clinical data of patients who underwent OPLF at two spine centers between June 2010 and June 2024. Patients were divided into readmission and non-readmission groups according to whether they were unplanned readmitted within 90 days of the primary surgery. Demographic and clinical outcomes were compared between the two groups. Multivariate logistic regression was used to analyze risk factors for 90-day readmission.ResultsOf the total, 8.6% (157/1826) of elderly patients experienced unplanned readmission within 90 days of the initial surgery. Factors including age, body mass index (BMI), American Society of Anesthesiologists (ASA) score (grade 3), history of diabetes, heart disease, respiratory disease, preoperative malnutrition, severe osteoporosis (T < −3.5), incidental durotomy, surgical segment, and surgical time in the readmission group were significantly higher than those in the non-readmission group. Multivariate logistic regression analysis suggested that higher age (p = 0.040, OR: 1.040, 95% CI: 1.002–1.079), ASA score ≥ grade 3 (p = 0.022, OR: 1.634, 95% CI: 1.074–2.485), heart disease (p = 0.021, OR: 1.971, 95% CI: 1.107–3.511), preoperative malnutrition (p = 0.028, OR: 1.701, 95% CI: 1.058–2.734), severe osteoporosis (p = 0.029, OR: 1.652, 95% CI: 1.054–2.588), surgical segment (p = 0.020, OR: 1.521, 95% CI: 1.067–2.169), and incidental durotomy (p = 0.012, OR: 2.193, 95% CI: 1.189–4.045) were risk factors for unplanned readmission.ConclusionWe identified seven risk factors associated with unplanned readmission within 90 days after OPLF in elderly patients. This information may assist clinicians in preoperative evaluations of patients to develop better surgical strategies.